Analysis of ebike dynamics and cyclists' anxiety levels and interactions with road vehicles that influence safety. (September 2021) - Pejhan, Shabnam; Agelin-Chaab, Martin; Yusuf, Munib; Eng, Donald
Highlights: Cyclists' mental stress is related to complex traffic scenarios despite lower speed. Type of overtaking vehicles showed an influence on the average heart rate of cyclists. Age had a main effect on mental workload and average heart rate during cycling on urban roads. Regardless of cycling skill, the perceived risk of riding in urban traffic was reported. Abstract: The significance of commuting with ebikes as an integral part of the urban mobility of the future can no longer be ignored. The real and perceived hazards of cycling in urban areas and sharing roads with other motorized vehicles have been identified as a major barrier to wider adoption of ebikes. The objective of this study is to investigate parameters that affect the anxiety level of cyclists, which influences their safety and interaction with other road users. An ebike was instrumented with a variety of sensors and equipment to monitor the speed, balance of bike, type, and proximity of vehicles overtaking cyclists, as well as the events on the road. Thirty-two participants rode the instrumented ebike for 12 km on urban roads in Oshawa, ON, Canada. Participants wore a heart rate sensor attached to their chest and a helmet equipped with a peripheral detection task setup to measure stress and mental workload. This naturalistic study showed that most participants had concerns about the threats and risks of crashes when sharing the road with other vehicles. The data showed that the significant difference in acceleration between ebikes and conventional bikes does not change the perception of safety for cyclists. Additionally, the outcomes indicate that mental workload and average heart rate increase at lower speeds when passing a queue of vehicles in traffic or at intersections. Across all participants, the balance of the bike did not change significantly. Also, neither the heart rate nor mental workload showed a significant effect on the balance of the bike. This study suggests that dense traffic in the afternoon and the demands of riding a bike in complex traffic conditions result in a higher mental workload even though cyclists slowed down their speeds. Furthermore, the majority reported perceived risks of cycling on a shared road with other vehicles regardless of the demographic differences. The findings from this study can be used as a framework for the development of active safety features for ebikes.